Knowledge and Attitudes towards Antibiotic Use among Non-Health Undergraduate Students at Andalas University - Dian Ayu Juwita; Dedy Almasdy; Maharani Reskia Fitri (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
The knowledge and understanding of the community about antibiotic usage are crucial to avoid inaccuracies in drug utilization. Negative impacts that can arise include the occurrence of resistance and the reduction in antibiotic effectiveness. Students with non-health related educational backgrounds are among the parts of the community that have a limited grasp of issues related to antibiotic usage. The aim of this research is to assess the level of knowledge and attitudes of non-health related major students towards antibiotic usage. This study utilized a cross-sectional method with validated questionnaires. Inclusion criteria for this research were non-health undergraduate students at Andalas University who were willing to complete the questionnaire comprehensively. The obtained data were statistically analyzed using SPSS version 26. The research findings indicate that non-health related major students at Andalas University possess moderate knowledge (54.7%) while their attitudes tend to be positive (71.1%) towards antibiotic usage. A significant correlation between students' knowledge and attitudes towards antibiotic usage was found, with a p-value 0.05. There was no significant correlation found between students' sociodemographic characteristics (faculty, age, gender, presence of family members working in the healthcare field) and their knowledge level. However, concerning attitudes, factors that influence include gender and the presence of family members working in the healthcare field.